A preparation method of a copper-doped amorphous zirconium dioxide catalyst and application thereof in electrocatalytic reduction of carbon dioxide

CN122879748APending Publication Date: 2026-10-09HUIZHOU INSTITUTE OF GREEN ENERGY & ADVANCED MATERIALS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611018975.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

铜基催化剂电催化还原CO2时的产物的包括甲烷(CH4)和乙烯(C2H4),CH4产物和C2H4产物之间的竞争反应导致很难得到较高选择性的单一产物

Benefits of technology

1.使用本发明提供的铜掺杂无定形二氧化锆催化剂进行电催化还原二氧化碳过程中,能大幅提高甲烷产率,同时实现了高甲烷选择性(法拉第效率最高达69.3%)、高甲烷分电流密度(-372.8 mA /cm2)以及优异的长期稳定性,在-300 mA /cm2下能稳定运行90小时以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879748A_ABST
    Figure CN122879748A_ABST
Patent Text Reader

Abstract

The present application relates to a copper-doped amorphous zirconium dioxide catalyst, wherein the zirconium dioxide in the copper-doped amorphous zirconium dioxide catalyst is in an amorphous structure, and copper elements are uniformly distributed in the zirconium dioxide in a doped form, and the copper elements exist in the form of Cu + and / or Cu 0 . The present application also relates to a preparation method of the copper-doped amorphous zirconium dioxide catalyst, and an application of the copper-doped amorphous zirconium dioxide catalyst in electrocatalytic reduction of carbon dioxide. The copper-doped amorphous zirconium dioxide catalyst has excellent stability, and in the process of electrocatalytic reduction of carbon dioxide using the copper-doped amorphous zirconium dioxide catalyst, high methane selectivity and high methane partial current density are simultaneously achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic reduction of carbon dioxide, specifically to a copper-doped amorphous zirconium dioxide electrocatalyst and its preparation method, as well as the application of the copper-doped amorphous zirconium dioxide catalyst in the electrocatalytic reduction of carbon dioxide to methane. Background Technology

[0002] This section provides background information relevant to this application, which does not necessarily constitute prior art.

[0003] With the massive consumption of fossil fuels, the concentration of carbon dioxide (CO2) in the atmosphere continues to rise, leading to serious environmental problems and an energy crisis. Electrochemical CO2 reduction reaction (CO2RR) driven by renewable electricity is an effective way to convert CO2 into high-value-added chemicals and achieve carbon cycling. Among the many products, methane (CH4) is an ideal fossil fuel substitute due to its high energy density (55.5 MJ / kg) and good compatibility with existing natural gas infrastructure. However, the conversion of CO2 to CH4 involves a complex eight-electron / eight-proton transfer process with slow reaction kinetics, requiring the development of highly active and selective electrocatalysts. Currently, catalysts for the electroreduction of CO2 to methane generally suffer from low selectivity, low current density, and insufficient stability, making it difficult to meet industrial requirements.

[0004] Existing copper-based catalysts used for the electrocatalytic reduction of CO2 often face problems such as high overpotential and low selectivity. The products of the electrocatalytic reduction of CO2 by copper-based catalysts include methane (CH4) and ethylene (C2H4). The competitive reaction between the CH4 and C2H4 products makes it difficult to obtain a single product with high selectivity. Simultaneously, the competition between the hydrogenation reaction of the CO2 reduction intermediate and the hydrogen evolution reaction at the copper electrode results in a low rate and poor selectivity for the conversion of CO2 into hydrocarbon products.

[0005] Existing metal oxide supports include alkali metal oxides, alkaline earth metal oxides, main group metal oxides, transition metal oxides, and lanthanide metal oxides. Among them, zirconium dioxide (ZrO2) is a common metal oxide support with advantages such as tunable structure, good stability, and strong interaction with active metal components. Studies have shown that the crystal structure of ZrO2 has a significant impact on catalytic performance. Compared with crystalline metal oxides, amorphous metal oxides, due to their long-range disordered structure, can provide more unsaturated sites and defect centers, which is expected to improve catalytic kinetics and mass transfer efficiency. Currently, there are no reports on the efficient electroreduction of CO2 to methane using copper-doped amorphous zirconium dioxide electrocatalysts. Summary of the Invention

[0006] The first objective of this invention is to provide a copper-doped amorphous zirconium dioxide catalyst that can efficiently and selectively electrocatalytically reduce carbon dioxide to methane.

[0007] A second objective of this invention is to provide a method for preparing the copper-doped amorphous zirconium dioxide catalyst.

[0008] A third objective of this invention is to provide the application of the copper-doped amorphous zirconium dioxide catalyst in the electrocatalytic reduction of carbon dioxide.

[0009] To achieve the above objectives, the present invention provides the following technical solution: A copper-doped amorphous zirconium dioxide catalyst is characterized in that the zirconium dioxide (ZrO2) in the catalyst has an amorphous structure, and copper (Cu) is uniformly distributed in the amorphous zirconium dioxide structure as a dopant. Based on the total mass of the copper-doped amorphous zirconium dioxide catalyst, the copper content is 0.1 wt%-10 wt%, preferably 1 wt%-5 wt%, and more preferably 2 wt%-4 wt%. When the copper content is less than 0.1 wt%, the electrocatalytic activity of the copper-doped amorphous zirconium dioxide catalyst is significantly reduced, specifically manifested in a significant decrease in the current density and Faradaic efficiency (FE) of the electrocatalytic reduction of CO2 to CH4. When the copper content is greater than 10 wt%, the electrocatalytic reduction of CO2 to methane using this copper-doped amorphous zirconium dioxide catalyst easily produces multi-carbon products (ethylene or ethanol).

[0010] In one or more embodiments, the copper element in the copper-doped amorphous zirconium dioxide catalyst is Cu. + and / or Cu 0 It exists in the form of.

[0011] In one or more embodiments, the copper content is approximately 2.37 wt% based on the total mass of the copper-doped amorphous zirconium dioxide catalyst.

[0012] The present invention also provides a method for preparing the above-mentioned copper-doped amorphous zirconium dioxide catalyst, characterized in that it includes a step of synthesizing the copper-doped amorphous zirconium dioxide catalyst by a solvothermal reaction.

[0013] In one or more embodiments, the preparation method includes the following steps: Step S1: Dissolve the surfactant, zirconium source, copper source and precipitant in an alcohol solvent in sequence, stir until homogeneous, and obtain a mixed solution; Step S2: The mixed solution is transferred to a high-pressure reactor for a solvothermal reaction. Step S3: After the solvothermal reaction is completed, the resulting precipitate is separated, washed, and dried to obtain the copper-doped amorphous zirconium dioxide catalyst.

[0014] The surfactant mentioned above includes F127 (Pluronic F127).

[0015] The zirconium source includes at least one of zirconium tetrachloride, zirconium nitrate, zirconium sulfate, zirconium acetate and their hydrates, preferably zirconium tetrachloride (ZrCl4).

[0016] The copper source includes at least one of copper acetate, copper chloride, copper nitrate, copper sulfate and their hydrates. Preferably, the copper source includes copper acetate tetrahydrate (Cu(CH3COO)2·4H2O).

[0017] The precipitant includes hexamethylenetetramine (HMT).

[0018] The alcohol solvent includes an aqueous solution of ethanol and / or an aqueous solution of ethylene glycol. Preferably, the alcohol solvent includes an aqueous solution of ethanol, and the volume ratio of ethanol to water is (30-40):(1-5), more preferably 35:2.

[0019] In step S1, the mass-volume ratio of the surfactant to the alcohol solvent is (0.2-0.6) g:(30-40) mL, more preferably 0.4 g:35 mL; the mass ratio of the zirconium source to the copper source is adjusted based on the requirement that the copper content in the final copper-doped amorphous zirconium dioxide catalyst is about 0.1 wt% to about 10 wt%, for example, the mass ratio of the zirconium source to the copper source can be controlled as (0.20-0.35):(0.05-0.40), preferably (0.28):(0.06-0.36), more preferably 0.28:0.24; the mass ratio of the zirconium source, copper source and precipitant is preferably (0.20-0.35):(0.05-0.40):(0.10-0.25), more preferably 0.28:0.24:0.16.

[0020] In step S2, the temperature of the solvothermal reaction is 120-200 ℃, preferably 160-180 ℃, more preferably 170 ℃; the reaction time of the solvothermal reaction is 2-12 h, preferably 3-6 h, more preferably 4 h.

[0021] In step S3, the drying is vacuum drying at 40-80 °C for 6-24 h, preferably vacuum drying at 60 °C for 12-24 h.

[0022] It should be noted that the copper-doped amorphous zirconium dioxide catalyst provided by this invention can be used to prepare copper-doped crystalline zirconium dioxide electrocatalysts. For example, the copper-doped amorphous zirconium dioxide catalyst can be obtained by calcining it at 500-700℃ (e.g., 600℃) for 2-6 h (e.g., 4 h) under an inert atmosphere (e.g., nitrogen) to obtain a copper-doped crystalline zirconium dioxide electrocatalyst. Unexpectedly, it was found that the copper-doped amorphous zirconium dioxide catalyst provides a more favorable catalytic microenvironment compared to the copper-doped crystalline zirconium dioxide electrocatalyst, thereby significantly improving the methane yield, indicating that the crystallinity of zirconium dioxide has a crucial influence on catalytic performance.

[0023] It should be noted that the copper-doped amorphous zirconium dioxide catalyst provided by this invention can be used to prepare electrodes. For example, the copper-doped amorphous zirconium dioxide catalyst can be loaded onto a conductive substrate (e.g., carbon paper / glassy carbon electrode, metal foam, etc.) using drop-coating, spraying, or spin-coating methods to construct an electrode for electrochemical reactions. This electrode can be used for the electroconversion of carbon dioxide. The preferred loading amount of the copper-doped amorphous zirconium dioxide catalyst on the conductive substrate is 0.1-10 mg / cm³. 2 More preferably 1 mg / cm 2 .

[0024] This invention also provides the application of the copper-doped amorphous zirconium dioxide catalyst in the electrocatalytic reduction of carbon dioxide. During the electrocatalytic reduction of CO2 using the copper-doped amorphous zirconium dioxide catalyst, the conversion of CO2 to CH4 products can be achieved, exhibiting high selectivity and stability.

[0025] In one or more embodiments, the copper-doped amorphous zirconium dioxide catalyst is dispersed in an organic solvent, wherein the organic solvent is one or a mixture of two or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, dichloromethane, N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC), and then Nafion binder is added and ultrasonically dispersed for 0.1-1 h to prepare a catalyst slurry. The catalyst slurry is uniformly coated on conductive carbon paper and dried to obtain a gas diffusion electrode for electrocatalytic reduction of CO2. In the process of electrocatalytic reduction of CO2, the conversion of CO2 to CH4 products can be realized.

[0026] In one or more embodiments, a three-electrode system is used for the electrocatalytic reduction of carbon dioxide. A glassy carbon electrode with a copper-doped amorphous zirconium dioxide catalyst supported on its surface serves as the working electrode and cathode; a platinum sheet electrode serves as the counter electrode and anode; and an Hg / HgO electrode or a saturated calomel electrode serves as the reference electrode. At 25°C and atmospheric pressure, an H-type electrolytic cell is used for the electrocatalytic reduction of CO2. The two chambers are separated by a Nafion membrane. The electrolyte solutions in both chambers are alkaline aqueous solutions, specifically one or a mixture of two or more of the following: KHCO3 solution, KCl solution, K2SO4 solution, KI solution, KCs solution, KBr solution, KF solution, KClO4 solution, and KOH solution. Preferably, the alkaline aqueous solution is a 0.1-1.0 M KOH solution, more preferably a 1 M KOH solution. One or more of He, N2, and Ar gases are introduced into the anode side, while a raw material gas is introduced into the cathode side. The raw material gas is pure CO2 or a mixture of CO2 with one or more of H2, O2, N2, NH3, Ar, and He, with a CO2 volume fraction of 50%-100%. CO2 is introduced into the electrolytic cell at atmospheric pressure until saturation, and then constant potential electrolysis is performed. The constant potential control range of the reaction system is 0V-(-2.0)V.

[0027] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: 1. The copper-doped amorphous zirconium dioxide catalyst provided by this invention significantly improves methane yield during the electrocatalytic reduction of carbon dioxide, while achieving high methane selectivity (Faraday efficiency up to 69.3%) and high methane partial current density (-372.8 mA / cm²). 2 It also exhibits excellent long-term stability at -300 mA / cm². 2 It can operate stably for more than 90 hours.

[0028] 2. The preparation method of the copper-doped amorphous zirconium dioxide catalyst provided by the present invention is a solvothermal method, which is simple, mild, and reproducible, and has good potential for industrial application. Attached Figure Description

[0029] The accompanying drawings further illustrate the invention, but the embodiments in the drawings do not constitute any limitation on the invention.

[0030] Figure 1 This is a transmission electron microscope (TEM) image of the Cu-aZrO2 catalyst prepared in Example 1 of the present invention.

[0031] Figure 2The high-resolution transmission electron microscope (HRTEM) image and selected area electron diffraction (SAED) pattern (top right inset) of the Cu-aZrO2 catalyst prepared in Example 1 of this invention show its amorphous characteristics.

[0032] Figure 3 The image shows the X-ray diffraction (XRD) pattern of the Cu-aZrO2 catalyst prepared in Example 1 of this invention.

[0033] Figure 4 This is an elemental distribution (EDS Mapping) diagram of the Cu-aZrO2 catalyst prepared in Example 1 of this invention.

[0034] Figure 5 This is a comparison chart of the Faradaic efficiencies of the Cu-aZrO2 catalyst prepared in Example 1 of the present invention and the crystalline copper-doped zirconium dioxide (Cu-cZrO2) catalyst prepared in Comparative Example 1 at different potentials for the electroreduction of CO2 products.

[0035] Figure 6 This is a comparison of the methane current density of the Cu-aZrO2 catalyst and the Cu-cZrO2 catalyst prepared in Example 1 of this invention.

[0036] Figure 7 The diagram shows the methane Faraday efficiency of the Cu-aZrO2 catalyst prepared in Example 1 of this invention under different copper contents.

[0037] Figure 8 The diagram shows the methane fractional current density of the Cu-aZrO2 catalyst prepared in Example 1 of this invention under different copper contents.

[0038] Figure 9 This is a graph showing the long-term stability test of the Cu-aZrO2 catalyst prepared in Example 1 of this invention. Detailed Implementation

[0039] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0040] [Example 1: Preparation of copper-doped amorphous zirconium dioxide catalyst] First, 0.4 g of surfactant F127 was completely dissolved in 35 mL of ethanol, and 2 mL of deionized water was added. The mixture was stirred continuously at room temperature to form a clear solution. Then, 0.28 g of ZrCl4 (zirconium source), 0.24 g of Cu(CH3COO)2·4H2O (copper source), and 0.16 g of HMT (precipitant) were added sequentially, and the mixture was stirred for another 30 minutes. Next, 30 mL of ethylene glycol was added to the mixture, and the mixture was stirred at room temperature for 24 h.

[0041] The final mixture was transferred to a 100 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene (PTFE), sealed, and placed in an oven at 170 °C for 4 h. After the reactor cooled naturally to room temperature, the precipitate was collected by centrifugation (10,000 rpm, 5 min) and washed several times with deionized water and ethanol. Finally, the washed precipitate was dried overnight in a vacuum drying oven at 60 °C to obtain the copper-doped amorphous zirconium dioxide catalyst, denoted as Cu-aZrO2.

[0042] The Cu-aZrO2 catalyst prepared in this embodiment was characterized. Figure 1 For TEM images, Figure 2 The images are HRTEM and SAED diagrams (inset in the upper right corner). Figure 3 For XRD patterns, Figure 4 This is an EDS mapping diagram. (By...) Figure 1 It can be seen that Cu-aZrO2 consists of aggregated nanoparticles; from Figure 2 and Figure 3 It can be seen that it has an amorphous structure; from Figure 4 It can be seen that Zr, Cu, and O elements are evenly distributed.

[0043] [Comparative Example 1: Preparation of Copper-Doped Crystalline Zirconium Dioxide Catalyst] The Cu-aZrO2 catalyst prepared in Example 1 was placed in a tube furnace and heated to 600°C at a heating rate of 5°C / min under a N2 atmosphere, and then calcined at that temperature for 4 h. After natural cooling, the resulting product was a crystalline copper-doped zirconium dioxide catalyst, denoted as Cu-cZrO2.

[0044] [Comparison Test] The following comparative tests were performed on the copper-doped amorphous zirconium dioxide catalyst (Cu-aZrO2) provided in Example 1 and the copper-doped crystalline zirconium dioxide catalyst (Cu-cZrO2) provided in Comparative Example 1. (1) Electrocatalytic carbon dioxide reduction test Electrode preparation: 2 mg of Cu-aZrO2 catalyst / Cu-cZrO2 catalyst was dispersed together with 15 μL of Nafion D-521 dispersion (5 wt%) in 0.7 mL of isopropanol and sonicated for 30 minutes to form a uniform catalyst ink. The ink was then uniformly drop-coated onto a gas diffusion layer carbon paper (1 × 1 cm). 2 The catalyst was dried at room temperature to obtain the working electrode, with a catalyst loading of approximately 1 mg / cm³. 2 .

[0045] Electrochemical testing: CO2 RR was tested in a three-electrode flow electrolytic cell. The prepared electrode was used as the working electrode, a Pt sheet as the counter electrode, and Hg / HgO as the reference electrode. The electrolyte was a 1 M KOH aqueous solution. CO2 was continuously introduced into the cathode chamber at a flow rate of 40 mL / min. Potentiostatic electrolysis tests were performed using an electrochemical workstation.

[0046] The results are as follows Figure 5 and Figure 6 As shown, the Cu-aZrO2 catalyst achieved a maximum Faradaic efficiency (FECH4) of 69.3% for the electroreduction of CO2 to methane at a potential of -1.2 V vs. RHE, with a methane partial current density (jCH4) reaching -372.8 mA / cm². 2 In contrast, the crystalline comparative Cu-cZrO2 catalyst exhibited a maximum FECH4 content of only 38.9% and a jCH4 content of -153.6 mA / cm² at -1.3 V. 2 .

[0047] [Example 3: Preparation of catalysts with different copper contents] Following the steps of Example 1, only the amount of copper source Cu(CH3COO)2·4H2O added was varied, with 0 g, 0.06 g, 0.12 g, 0.30 g, and 0.36 g added respectively, to synthesize a series of catalysts with different Cu doping amounts. The actual copper mass fractions, determined by inductively coupled plasma optical emission spectrometry (ICP-OES), were 0 wt%, 0.82 wt%, 1.5 wt%, 2.37 wt%, and 4.24 wt%, respectively. Figure 7 and Figure 8 As shown, the catalyst with a copper content of 2.37 wt% exhibits the best performance in CO2 reduction to methane.

[0048] [Example 4: Long-term stability test] The long-term stability of the Cu-aZrO2 catalyst prepared in Example 1 was evaluated using the galvanostatic method, such as... Figure 9 As shown, at -300 mA / cm 2 After running continuously for 90 h at a constant current density, neither the applied potential nor the Faraday efficiency of methane showed significant changes, indicating that the catalyst has good electrochemical stability.

[0049] [Example 5: Preparation of catalysts with different metal oxide supports] Following the steps in Example 1, the following catalysts were prepared and subjected to electrocatalytic carbon dioxide reduction tests.

[0050] Sample 1: The only difference from Example 1 is that ZrCl4 (zirconium source) is replaced with AlCl3; Sample 2: The only difference from Example 1 is that ZrCl4 (zirconium source) is replaced with TiCl3; Sample 3: The only difference from Example 1 is that ZrCl4 (zirconium source) is replaced with CeCl3; Sample 4: The only difference from Example 1 is that ZrCl4 (zirconium source) is replaced with CrCl3.

[0051] The catalysts provided in samples 1-4 were supported by metal oxides Al₂O₃, TiO₂, CeO₂, and Cr₂O₃, respectively. Following the test methods described in the comparative test, the CO₂RR of the catalysts in samples 1-4 was tested in an electrolytic cell using a 1 M KOH aqueous solution. CO₂ was continuously introduced into the cathode chamber at a flow rate of 40 mL / min, and electrolysis was performed at a constant voltage of -1.2 V vs. RHE potential for 4 hours. Gas products were collected every hour for analysis. The test results are as follows: Sample 1: The Faraday efficiency (FECH4) for the electroreduction of CO2 to methane was 20.1%, and the methane portion current density (jCH4) reached -106.7 mA / cm². 2 ; Sample 2: The Faraday efficiency (FECH4) for the electroreduction of CO2 to methane was 34.5%, and the methane current density (jCH4) reached -126.8 mA / cm². 2 ; Sample 3: The Faraday efficiency (FECH4) for the electroreduction of CO2 to methane was 31.3%, and the methane portion current density (jCH4) reached -113.4 mA / cm². 2 ; Sample 4: The Faraday efficiency (FECH4) for the electroreduction of CO2 to methane was 18.2%, and the methane current density (jCH4) reached -100.5 mA / cm². 2 .

[0052] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0053] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A copper-doped amorphous zirconium dioxide catalyst, characterized in that, The zirconium dioxide in the copper-doped amorphous zirconium dioxide catalyst has an amorphous structure, and copper is uniformly distributed in the zirconium dioxide as a dopant. The copper element is Cu. + and / or Cu 0 It exists in the form of.

2. The copper-doped amorphous zirconium dioxide catalyst according to claim 1, characterized in that, Based on the total mass of the copper-doped amorphous zirconium dioxide catalyst, the copper content is 0.1 wt%-10 wt%.

3. The method for preparing the copper-doped amorphous zirconium dioxide catalyst according to claim 2, characterized in that, This includes the step of synthesizing a copper-doped amorphous zirconium dioxide catalyst via a solvothermal reaction.

4. The preparation method according to claim 3, characterized in that, Includes the following steps: Step S1: Dissolve the surfactant, zirconium source, copper source and precipitant in an alcohol solvent in sequence, stir until homogeneous, and obtain a mixed solution; Step S2: The mixed solution is transferred to a high-pressure reactor for a solvothermal reaction. Step S3: After the solvothermal reaction is completed, the resulting precipitate is separated, washed, and dried to obtain the copper-doped amorphous zirconium dioxide catalyst.

5. The preparation method according to claim 4, characterized in that, The surfactant includes F127; the zirconium source includes at least one of zirconium chloride, zirconium nitrate, zirconium sulfate, zirconium acetate, and their hydrates; the copper source includes at least one of copper acetate, copper chloride, copper nitrate, copper sulfate, and their hydrates; the precipitant includes hexamethylenetetramine; and the alcohol solvent includes an aqueous solution of ethanol and / or an aqueous solution of ethylene glycol.

6. The preparation method according to claim 4, characterized in that, In step S1, the mass-volume ratio of the surfactant to the alcohol solvent is (0.2-0.6) g: (30-40) mL; the mass ratio of the zirconium source to the copper source is (0.20-0.35): (0.05-0.40); and the mass ratio of the zirconium source, the copper source, and the precipitant is (0.20-0.35): (0.05-0.40): (0.10-0.25).

7. The preparation method according to claim 4, characterized in that, In step S2, the temperature of the solvothermal reaction is 120-200 °C, and the reaction time is 2-12 h.

8. The preparation method according to claim 4, characterized in that, In step S3, the drying is performed under vacuum at 40-80°C for 6-24 hours.

9. The application of the copper-doped amorphous zirconium dioxide catalyst according to claim 2 in the electrocatalytic reduction of carbon dioxide.

10. The application according to claim 9, characterized in that, In the process of electrocatalytic reduction of carbon dioxide using the copper-doped amorphous zirconium dioxide catalyst, the conversion of carbon dioxide to methane products is achieved.